Factors Affecting Elite Sports Development in the Philippines: A Delphi study - TULIAO,; Darwin, Robin (International Journal of Psychosocial Rehabilitation, 2020)
For several years in the past, Philippines has not recorded success in terms of the development of elite sports in the the South East Asian Games (SEAG), Olympic and Asian Games. When it comes to elite sports, history would tell that the country’s sports achievement has been fluctuating. This study used a qualitative research. Also, a three-round Delphi survey approach was used to generate responses and achieve consensus from a selected group of experts such as government administrators, national coaches, olympian athletes, sports journalist and physical educators. The experts identified eleven direct factors, such as policies in sports, grassroots program and nine indirect factors like government service, economic condition and others that affect the development of elite sports in the Philippines. The study found out that the main factor in affecting elite sport in the Philippines was coming from the support of the government and non-government (directly) and National Sports Association leadership (indirectly). However the Political interest (directly) and Red tape (indirectly) are found to have the least that affects elite sports in the country. It was found out that factors such as mentioned above have significant effect on the Philippine’s performance towards the development of elite sports as stated by the experts who were participants of the study.